Мохоподібні національного природного парку “Деснянсько-Старогутський” (Сумська обл., Україна) - ВІРЧЕНКО, ВІТАЛІЙ МИХАЙЛОВИЧ; ПАНЧЕНКО, СЕРГІЙ МИХАЙЛОВИЧ (CHORNOMORSKI BOTANICAL JOURNAL, 2005)
Мохоподібні національного природного парку “Деснянсько-Старогутський” (Сумська обл., Україна)